Simulation of operating conditions and working fluids for organic Rankine cycles - Hernández-Fernández, Nerio José; Zumalacárregui-de Cárdenas, Lourdes; Pérez-Ones, Osney (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Operating conditions for different fluids in Organic Rankine Cycles using low grade energies were compared. The following fluids were used: R152a (1,1-difluroethane), R-290 (propane), R-600a (2-methylpropane or isobutane), R-744 (CO2) y R-1270 (propylene). Simulation with HYSYS v3.2 was used to support the research. Organic Rankine cycle was studied. Also, the following modifications were studied: reheating, regeneration and reheating-regeneration. Regeneration cycle showed the best results, however, thermal efficiencies were lower than 10%. Operating conditions were simulated in order to increase this value. It was determined that the fluid that presented the best behavior was the R-600a refrigerant, using a Rankine with regeneration cycle operating between 3 500 kPa and 150 ºC at the turbine entrance and 700 kPa in the condenser. A thermal efficiency of 15.33 % was obtained and 7.11 kW of electric power can be produced.